Speech therapy assesement of non-nutritive sucking and neurodevelopment relationship in preterm children - Ordóñez-Miyar, Belén D.; Periáñez, José A.; Blanco, Dorotea; Romero-Gómez, Bárbara; Valverde-López, Belén; Vellosillo, Perceval; Carricondo, Francisco (Revista de Investigación en Logopedia, 2025)
Sucking is a reflex necessary for survival, and premature infants often have problems developing it. Furthermore, it is a primary expression of brain function, leading to an increasing number of studies linking it to general movements (GM) and later neurodevelopment. Currently, the most widely used tool for assessing this is the NOMAS scale, but sucking patterns described on this scale as disorganized show an unreliable correlation with neurodevelopment. Therefore, a more in-depth analysis of the evolution of non-nutritive sucking (NNS) in relation to GM was proposed, in order to provide early predictive value. For this purpose, a prospective longitudinal descriptive study was carried out, with 66 premature participants
Keywords: General movements; Neurodevelopment; Non-nutritive sucking; Preterm; Speech and Language Therapy